KERAGAMAN KAPANG PADA TANAH RIZOSFER TANAMAN TOMAT DI LAHAN PERTANIAN KONVENSIONAL - RIAJENG KRISTIANA (Faktor Exacta, 2015)
Moulds were isolated from rhizosphere of tomato plants growing in the Villages of Cikahuripan, Sukabumi. Twenty six isolates were identified from 43 isolates that isolated from rhizosphere of tomato plant. That isolates including 8 species which is Aspergillus fumigatus Fres. (7 isolates), Aspergillus niger Van Tieghem (1 isolate), Aspergillus tamarii Kita (1 isolate), Aspergillus sp. (3 isolate), Fusarium oxysporum Schlecht. (1 isolate), Humicola fuscoatra Traaen (7 isolates), Penicillium sp. 1 (4 isolates), Penicillium sp. 2 (2 isolates). Aspergillus fumigatus and H. fuscoatra dominated rhizosphere moulds in the Cikahuripan village. Aspergillus, Fusarium, Humicola, Penicillium is a part of Mitosporic Moulds. Aspergillus is mould that can find a lot which is 4 species. Key words : aspergillus sp., moulds rhizosphere, conventional farm